2013
DOI: 10.1088/0964-1726/22/11/115008
|View full text |Cite
|
Sign up to set email alerts
|

Power generation of a thermoelectric generator with phase change materials

Abstract: In this paper, a thermoelectric generator that embeds phase change materials for wasted heat energy harvesting is proposed. The proposed thermoelectric generator embeds phase change materials in its device structure. The phase change materials store large amounts of heat energy using the latent heat of fusion. When the heat source contacts the thermoelectric generator, dissipated heat from the heat source is stored in the phase change materials. When the heat source is removed from the thermoelectric generator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The sensors in such networks are usually battery-powered, which is environmentally harmful and shortperiod [1]. Harvesting energy from surroundings has demonstrated the potential to replace batteries in WSN applications [2][3][4][5][6][7][8], while vibration energy has also attracted the attention of several scientists, because of its prevalence in the environment as a form of waste energy.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors in such networks are usually battery-powered, which is environmentally harmful and shortperiod [1]. Harvesting energy from surroundings has demonstrated the potential to replace batteries in WSN applications [2][3][4][5][6][7][8], while vibration energy has also attracted the attention of several scientists, because of its prevalence in the environment as a form of waste energy.…”
Section: Introductionmentioning
confidence: 99%
“…PN TEGs are utilized as thermoelectric devices and two different PCM composites are connected to each side of PN TEGs [ 43 ]. PN TEGs possess a hot side and a cold side due to the internal structure of the N and P type semiconductors [ 44 , 45 ]. The electrons doped in the N type semiconductor start the excitation while absorbing the external thermal energy and move to the P type semiconductor [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single IT-TEG could generate a maximum instantaneous power of 2.08 mW in the process of SSAT phase change transition. Jo et al [17] proposed a TEG which was embedded with PCM for harvesting wasted heat energy. The experimental results showed that the TEG could continue generate electrical energy when the heat source was removed by the heat energy stored in the PCM.…”
Section: Introductionmentioning
confidence: 99%